1981
DOI: 10.3109/03009748109095325
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatic Disorders in Primary Care: A Study of Two Primary Care Centres and a Review of Previous Swedish Reports on Primary Care

Abstract: Utilization of care for rheumatic disorders was studied in two primary care units. In both units 12% of visits concerned some form of rheumatic disease. This diagnostic group (chapter XIII of ICD) ranked third after cardiovascular and respiratory diseases. The total number of visits per inhabitant was higher for all diagnoses, as well as for the rheumatic disorders, in the most remote primary care unit. The distribution of rheumatic diagnoses was similar in the two units. Back disorders were most frequent amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…More than 75% of patients show erosions within the Wrst 2 years of disease and structural damage contributes to approximately 25% of cumulative disability [3]. The beneWt of early therapy in the prevention of damage and disability has been clearly proven in several independent studies [1][2][3][4][5][6][7]. Mean lag time before diagnosis in our study was 40.5 months .…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…More than 75% of patients show erosions within the Wrst 2 years of disease and structural damage contributes to approximately 25% of cumulative disability [3]. The beneWt of early therapy in the prevention of damage and disability has been clearly proven in several independent studies [1][2][3][4][5][6][7]. Mean lag time before diagnosis in our study was 40.5 months .…”
Section: Discussionmentioning
confidence: 95%
“…In general, previous studies have shown poor agreement in the diagnosis of RA between primary care physicians and rheumatologists [1,15,[24][25][26][27][28][29]. Gamez-Nava et al…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Final diagnoses were arrived at by consensus among a group of specialists using accepted diagnostic criteria. 17,18 As all patients underwent complete reevaluation, bias introduced by knowing the referring physicians' diagnoses was minimized. The low rate of agreement between the referring and final diagnosis supports that conclusion.…”
Section: Commentmentioning
confidence: 99%
“…6 The majority of referrals to rheumatology originate in primary care; musculoskeletal disorders are estimated to account for up to 12% of visits to primary care physicians. 7 Many primary care physicians express low levels of confidence in their ability to recognize and manage musculoskeletal conditions, 8 which may account, in part, for the poor quality of referrals; data from the United Kingdom identified the absence of basic information in more than 50% of referrals. 9 A subsequent Canadian study has shown that the absence of historical and laboratory information can lead to the inappropriate triage of urgent referrals.…”
mentioning
confidence: 99%